Psychological components of professional-pedagogical culture ("Conference on Universal Science Research 2023", 2023)
This article discusses the role that psychological culture of class teacher plays in the establishment and maintenance of psychological safety in a modern schoolchild. The problem of protection against psychological abuse within the educational environment of a school is particularly important in the current socio-cultural realm. The article analyzes many pedagogical and psychological studies regarding the problem of psychological education of teachers.